Metallic W/WO2 solid-acid catalyst boosts hydrogen evolution reaction in alkaline electrolyte - Chen, Zhigang; Gong, Wenbin; Wang, Juan; Hou, Shuang; Yang, Guang; Zhu, Chengfeng; Fan, Xiyue; Li, Yifan; Gao, Rui; Cui, Yi (Nature communications, 2023)
The lack of available protons severely lowers the activity of alkaline hydrogen evolution reaction process than that in acids, which can be efficiently accelerated by tuning the coverage and chemical environment of protons on catalyst surface. However, the cycling of active sites by proton transfer is largely dependent on the utilization of noble metal catalysts because of the appealing electronic interaction between noble metal atoms and protons. Herein, an all-non-noble W/WO 2 metallic heterostructure serving as an efficient solid-acid catalyst exhibits remarkable hydrogen evolution reaction performance with an ultra-low overpotential of −35 mV at −10 mA/cm 2 and a small Tafel slope (−34 mV/dec), as well as long-term durability of hydrogen production (>50 h) at current densities of −10 and −50 mA/cm 2 in alkaline electrolyte. Multiple in situ and ex situ spectroscopy characterizations combining with first-principle density functional theory calculations discover that a dynamic proton-concentrated surface can be constructed on W/WO 2 solid-acid catalyst under ultra-low overpotentials, which enables W/WO 2 catalyzing alkaline hydrogen production to follow a kinetically fast Volmer-Tafel pathway with two neighboring protons recombining into a hydrogen molecule. Our strategy of solid-acid catalyst and utilization of multiple spectroscopy characterizations may provide an interesting route for designing advanced all-non-noble catalytic system towards boosting hydrogen evolution reaction performance in alkaline electrolyte. The high cost and low abundance of noble metals largely restrict practical applications for electrochemical hydrogen production. Here, the authors prepare ultrasmall tungsten nanoparticles on metallic tungsten dioxide nanorods and demonstrate excellent activities for the alkaline hydrogen evolution reaction.